Unions and Firms' Investments: A Unified View - Fabio Berton; Stefano Dughera; Andrea Ricci (Institute of Labor Economics (IZA), 2019)
In this paper, we present a simple model in which a unionized and non-unionized firm optimally make investment decisions given their labor productivity. By allowing workers' organizations to have positive effects on labor effort, we find that the classic hold-up problem does not necessarily survive. We also derive conditions under which rent-seeking by unions may actually encourage firms' investments.
Keywords: J51; O31; O32; 330; labor unions; rent seeking; workers' effort; firms' investments; hold-up